1998
DOI: 10.1143/jjap.37.4158
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties of Crystalline CeO2 Films Formed by Metalorganic Decomposition

Abstract: Crystalline CeO2 films were formed on a Si (100) substrate by metalorganic decomposition at temparatures ranging from 600°C to 800°C. As-deposited films were in the amorphous state and were completely transformed to crystalline CeO2 above 600°C. However, during crystallization in oxygen atomosphere, a reaction between CeO2 and Si occurred at the interface, which resulted in the formation of a thin interfacial SiO2 layer. Capacitance-voltage measurement on these films showed good dielectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…Four diffraction peaks, which were ascribed to cubic phases of CeO 2 , were detected at (1 1 1), (2 0 0), (2 2 0) and (3 1 1). These peaks were similar to those reported in CeO 2 -Si system [35,43]. The CeO 2 (2 0 0) diffraction peak becomes sharper with the increase in annealing temperature but not much changes in intensity for other CeO 2 peaks.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Four diffraction peaks, which were ascribed to cubic phases of CeO 2 , were detected at (1 1 1), (2 0 0), (2 2 0) and (3 1 1). These peaks were similar to those reported in CeO 2 -Si system [35,43]. The CeO 2 (2 0 0) diffraction peak becomes sharper with the increase in annealing temperature but not much changes in intensity for other CeO 2 peaks.…”
Section: Resultssupporting
confidence: 87%
“…These properties have promoted CeO 2 as an alternative gate to SiO 2 . Previously, a large body of work has been carried out on CeO 2 film deposited on Si substrate using various deposition techniques, such as spray pyrolysis, electron beam evaporation, reactive sputtering, ion-beam sputtering, metal-organic decomposition (MOD), pulsed laser deposition and others [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Among these techniques, MOD method appears to be a convenient route due to its simplicity in processing control and accuracy in composition control [49] if compared to vacuum techniques, such as reactive sputtering and electron beam evaporation [34,37,40].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some papers have shown that the crystalline quality of the CeO 2 films grown on (1 1 1) Si substrate is better for a high growth temperature [24] and that the crystallinity is improved by a post deposition rapid thermal annealing [35]. Most of the time, studies on the influence of thermal annealing highlight the impact of the annealing time and annealing temperature on the crystallinity [36] and on the electrical properties [37] of the CeO 2 layers. All these papers show the importance of the post-growth annealing in microelectronic process.…”
Section: Introductionmentioning
confidence: 99%